Management Strategies for Growing Skull Fractures: A Single-Center Experience - Velho, Vernon; Kharosekar, Hrushikesh U.; Naik, Harish; Valsangkar, Shonali; Survashe, Pravin (Indian Journal of Neurotrauma, 2016)
Introduction Growing skull fractures are a rare but significant complication of pediatric head trauma, occurring mostly in children. Growing skull fractures are associated with a breach in the dura underlying the fracture line and may exceed the line of fracture making the management difficult. A delay in diagnosis exacerbates this disease increasing morbidity.Materials and Methods A retrospective analysis of 36 patients who were operated for growing skull fracture between August 2005 and August 2015 in our institute was done.Results Most common age group at presentation was 1 to 6 months and fall from height was the most common etiology. All patients underwent surgical repair; 23 required only duraplasty whereas cranioplasty with dural repair was done at the same time in 13 patients. Osteomesh, titanium mesh, and autologous bone chips were used for cranioplasty. All patients who presented to us with scalp swelling had complete resolution of swelling, whereas of the 7 patient who had neurologic deficit, 5 improved postoperatively (71%). Good clinical outcome was obtained in all patients.Conclusion Herniation of the brain matter and underlying dural tear, which can extend beyond the bony defect makes management challenging in growing skull fracture.
Keywords: growing skull fracture; Osteomesh; titanium mesh; duraplasty; children